Past tree range dynamics in the Iberian Peninsula inferred through phylogeography and palaeodistribution modelling: A review - Rodríguez-Sánchez, Francisco; Hampe, Arndt; Jordano, Pedro; Arroyo, Juan (Review of Palaeobotany and Palynology, 2010)
The forests in the Iberian Peninsula have been strongly inﬂuenced by past climatic changes, but reconstructing their historical distributions and dynamics is very difﬁcult due to the complex climatic characteristics and relief of the region. Research disciplines such as phylogeography and species distribution modelling can describe the past range dynamics of individual tree species in relatively great detail and help elucidate how these species have reacted to climatic changes. Here we review phylogeographical and modelling studies from species representative of the major Iberian forest types and attempt to extract general trends from the diversity of individual species histories in the Peninsula. To date most studies focus on geographical range dynamics during the Pleistocene, but an increasing body of evidence shows that some species have also retained the genetic imprints of much more ancient processes. Many widespread Iberian species show a deep and often remarkably clear-cut divide between populations from the Mediterranean and from the Atlantic regions of the Iberian Peninsula, suggesting that both areas have independently sustained viable populations over extended periods. In fact, phylogeographical studies commonly ﬁnd that species had several glacial refugia across the Iberian Peninsula. On the other hand, distribution models help identifying further suitable areas that could have sustained so far undetected refugia. Such studies are of interest for species conservation, because refugium populations are high-priority targets due to their longterm persistence and unique evolutionary trajectory. Overall, we conclude that palaeoecology, phylogeography and species distribution modelling have a great potential to inform each other because of their complementary perspectives and results. A true integration of these approaches is therefore fundamental for further progress in our understanding of past Iberian environments and the organisms they harboured.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: genetic diversity; glacial refugia; hindcasting; palaeobiogeography; Spain; species distribution modelling

Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling

Predictive modelling of tree species distributions on the Iberian Peninsula during the Last Glacial Maximum and Mid-Holocene - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Ecography, 2007)
This paper reports a bioclimatic envelope model study of the potential distribution of 19 tree species in the Iberian Peninsula during the Last Glacial Maximum (LGM; 21 000 yr BP) and the Mid-Holocene (6000 yr BP). Current patterns of tree species richness and distributions are believed to have been strongly influenced by the climate during these periods. The modelling employed novel machine learning techniques, and its accuracy was evaluated using a threshold-independent method. Two atmospheric general circulation models, UGAMP and ECHAM3 (generated by the Palaeoclimate Modelling Intercomparison Project, PMIP), were used to provide climate scenarios under which the distributions of the 19 tree species were modelled. The results obtained for these scenarios were assessed by agreement measure analysis; they differed significantly for the LGM, but were more similar for the Mid-Holocene. The results for the LGM support the inferred importance of pines in the Iberian Peninsula at this time, and the presence of evergreen Quercus in the south. Important differences in the altitude at which the modelled species grew were also predicted. During the LGM, some normally higher mountain species potentially became re-established in the foothills of the Pyrenees. The warm Mid-Holocene climate is clearly reflected in the predicted expansion of broad-leaved forests during this period, including the colonization of the northern part of the Iberian Peninsula by evergreen Quercus species.
Keywords: climate scenarios; iberian peninsula; Pinus; Quercus; refugia (voyant); species distribution modelling